Initial adaptation of a questionnaire on selfperception of quality of life in patients with dysphagia - Toledo R., Lilian; Aguirre B., Inés; Scaramelli S., Michelle; Baeza P., Diego; Mella G., Julio; Munita G., Aline (Revista Chilena de Fonoaudiología, 2017)
The purpose of this study was to carry out an initial adaptation to the Chilean population of the Swallowing Quality of Life Questionnaire (SWAL-QOL) instrument designed to know the perception of quality of life in persons with oropharyngeal dysphagia. The adaptation of the instrument was carried out via translation and backtranslations, which resulted in a final version of the questionnaire through consensus of experts. It was applied to ten people with dysphagia due to stroke. The adaptation of the instrument was considered appropriate and values of internal consistency for all scales were adequate, with coefficients α Cronbach ranging between 0.71 and 0.90. Dysphagia patients reported a decrease in their perception of quality of life, with the lowest scores observed for feeding duration (47.00 ± 9.90) and mental health (48.00 ± 17.78). The present study presents an adapted version of the SWAL-QOL, which is easy to apply in clinical practice.